Capital controls and financial liberalization: Removing the ideological bias in light of the contribution of Keynes and others and the recent experience - André de Melo Modenesi; Rui Lyrio Modenesi (Institute for Applied Economic Research (ipea), 2015)
To label the defense of capital controls (CC) as a left-wing proposal is a misconstruction. Such labeling uses the Borsa economicist criterion, which reduces the dichotomy between right and left to a distinction between liberalism and interventionism. Yet, under this criterion, the use of CC cannot be labeled as a leftist proposal. The interventionism underlying the defense of CC, as pioneered by Keynes and developed by Tobin, Davidson, Stiglitz and Rodrik, is not the fruit of an ideological conviction favoring widespread and indiscriminate State intervention. For them, CC are instruments to be used under specific economic circumstances. To call CC a practice typical of left-wing governments is also a misinterpretation. Among the countries using strict forms of CC since the 1990's - Chile, China, India, Malaysia and Thailand - only China's government may be called leftist. The other countries' political panorama is more complex than may suppose those who believe in a simple and direct relationship between CC and political ideology. The discussion should be stripped of the prevalent ideological bias: CC are not inherent to the political leanings of the governments that adopt them but are an expedient used under a pragmatic justification. Recognizing this is an important step toward a more objective analysis of the incidental opportunity of using CC, without prejudice. CC should be used whenever the benefits surpass the costs of their implementation.
Keywords: F32; 330